2009
DOI: 10.1189/jlb.1108691
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-dependent mast cell death induced by Ag (I) via cardiolipin oxidation and ATP depletion

Abstract: In genetically susceptible humans and/or experimental animals, ions of heavy metals, Hg (II), Au (III), and Ag (I) have been shown to strongly induce autoimmunity, in which mast cells have been implicated to play a role. Here, we demonstrate that Ag (I) application results in mast cell death through a unique Ca(2+)- and mitochondria-dependent pathway. As cellular susceptibilities to Ag (I) cytotoxicity varied considerably, we analyzed the cell death pathway in the low and high responding cells. In the low resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Following exposure to AgNPs, and as quickly as 10 min, mast cells started to degranulate (Fig 1B) as evidenced by membrane blebbing and reduction in the number of granules present in the cells over time. It was previously shown that exposure to silver ions (Ag + ) induces mast cell apoptosis through cardiolipin oxidation and ATP depletion [30]. However, we assessed cellular toxicity in response to AgNPs (25 μg/ml) and found that 24 h exposure did not trigger any significant cell death (S1 Fig) suggesting a possible different mechanism between Ag + and AgNPs in mediating mast cell activation/toxicity.…”
Section: Resultsmentioning
confidence: 88%
“…Following exposure to AgNPs, and as quickly as 10 min, mast cells started to degranulate (Fig 1B) as evidenced by membrane blebbing and reduction in the number of granules present in the cells over time. It was previously shown that exposure to silver ions (Ag + ) induces mast cell apoptosis through cardiolipin oxidation and ATP depletion [30]. However, we assessed cellular toxicity in response to AgNPs (25 μg/ml) and found that 24 h exposure did not trigger any significant cell death (S1 Fig) suggesting a possible different mechanism between Ag + and AgNPs in mediating mast cell activation/toxicity.…”
Section: Resultsmentioning
confidence: 88%
“…Cell research. Ag + induced mitochondrial apoptosis in human Chang liver cells, Ewing's sarcoma A673 cells, A549 lung cancer cells, human airway smooth muscle, human breast SKBR3 cancer cells, histiocytic lymphoma U-937 cells, human promyelocytic HL-60 cells, human keratinocytes, CHO-K line cells, human bronchial epithelial BEAS-2B cells, human skin fibroblasts, and mouse AML12 hepatocytes [89][90][91][92][93][94][95][96][97][98][99][100][101][102]. The apoptosis manifested alongside decreased cell viability, caspase 3 and 7 activation, pro-apoptotic genes (Bax and Bcl-2) expression, increased metallothionein expression, ATP depletion, and DNA fragmentation.…”
Section: Modern Research On Heavy Metal Toxicitymentioning
confidence: 99%
“…These assays combined provide extensive information about mitochondrial distribution, fusion, fission, motility and calcium flux. [75][76][77] These dyes must be stored at 220 uC, in an anhydrous environment and protected from light, and their ester derivatives are susceptible to hydrolysis, particularly when found in solution. Another derivative is the known MitoRed, which notably has an ester function and must also be stored in the dark and frozen (2-8 uC).…”
Section: Commonly Used Commercial Mitochondrion-specific Markers Fixe...mentioning
confidence: 99%